Automatic gain control for multi-channel electrochemical detection system combining FPGA and FPAA - Xuhai Chen; Min Du (2012 5th International Conference on Biomedical Engineering and Informatics, 2012)
In this work we describe the design and engineering of a multi-channel adaptive electrochemical (EC) signal acquisition system both using Field Programmable Gate Array (FPGA) and Field Programmable Analog Array (FPAA). With inheriting the powerful properties from the above devices, it has both automatic gain and reconfigurable feature. The 16 uniform automatic gain control (AGC) modules in this system operate in parallel and set the gain automatically dependent on the input amplitude. Compared with most of the other AGC systems, the combined FPGA/FPAA implementation presented here operates without ADC sampling and software processing, so that the gain-setting time is minimized. Besides, the FPAA-based AGC system can be dynamically reconfigured for polymerase chain reaction (PCR) in future design without changing any hardware. For the simple but efficient control mechanism, most circuits of the system can be integrated into a small-scale FPGA chip and several FPAA chips. These characters make this detection system ideal for in-situ or fPield multi-channel EC-PCR measurements.